2004
DOI: 10.1021/jp040188z
|View full text |Cite
|
Sign up to set email alerts
|

Adsorption Site and Surface Temperature Effects in CO Formation on Pt(111):  A New Semiclassical Study

Abstract: This study focuses on the dynamics of CO formation on Pt(111). To this end, a new semiempirical interaction potential was derived by using much of the most recent experimental information obtained from CO chemisorbed on the on top and bridge platinum sites. The dynamics on the adiabatic potential surface has been performed according to the semiclassical collisional method developed for molecule−surface interactions. The role played by the multiphonon excitation mechanism, the adsorption site, and the surface t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…Devereux and Meuwly recently showed that Morse potentials are essential to describe CO vibrations in MbCO. 25 Ta k i n g their Morse constants for Fe-bound CO (D e = 230.0 kcal/mol, β = 2.1/Å), values for free CO (D e = 249.65 kcal/mol, β = 2.34/Å, reported in ref 26), and Franzen's x e values, one finds 85, 14, and 1%, which is very close to the above calculation. Thus, a derivation of vibrational populations from Morse potentials of Fe-bound and unbound CO molecules can reproduce our experimental data.…”
supporting
confidence: 82%
“…Devereux and Meuwly recently showed that Morse potentials are essential to describe CO vibrations in MbCO. 25 Ta k i n g their Morse constants for Fe-bound CO (D e = 230.0 kcal/mol, β = 2.1/Å), values for free CO (D e = 249.65 kcal/mol, β = 2.34/Å, reported in ref 26), and Franzen's x e values, one finds 85, 14, and 1%, which is very close to the above calculation. Thus, a derivation of vibrational populations from Morse potentials of Fe-bound and unbound CO molecules can reproduce our experimental data.…”
supporting
confidence: 82%
“…In the former case, instead of a single site the surface exhibits a distribution of active surface sites each of which having different binding energy and energy barriers to reactions. This effect has been also explored in semiclassical MD calculations for CO formation and CO oxidation catalyzed by Pt(111) [21].…”
Section: (Some) Cases Studiedmentioning
confidence: 99%
“…The method is quite involved from a formal point of view, nevertheless is computationally feasible and gives a realistic, accurate picture of the dynamics of the molecular surface processes. The method has been applied to the study of several heterogeneous systems assumed as prototype systems in molecular dynamics investigations: H 2 /Cu [7,8]; H/graphite [2,3], CO [9]; N,N 2 ,O,O 2 /SiO 2 [10,11].…”
Section: Molecular Dynamics Calculationsmentioning
confidence: 99%